Above- and below-ground interactions in teak-barley agroforestry system in the Bundelkhand region of Central India - Upadhyaya, K.; Ram, Asha; Dev, Inder; Kumar, Naresh; Upadhyaya, S.; Gautam, Kamini; Arunachalam, A. (Indian Journal of Agroforestry, 2021)
The present study was aimed to optimize productivity of teak (Tectona grandis L.f.) based agroforestry system by evaluating some above- and below-ground interactions and their effects on growth and yield of intercropped barley (Hordeum vulgare L.). Sixteen treatment combinations comprising of four distances (D1- 1 m, D2- 2 m, D3- 3 m and D4- 4 m) away from treebase and four directions (East, West, North and South) were evaluated using Factorial Randomized Block Design with three replications. Data on light interception (Hz), plant height (cm), chlorophyll content (SPAD value), soil moisture (%) and grain yield (g m-2) were collected and analysed. Light interception reached at its peak at 12.00 noon and lowest at 5.00 pm. At its peak, highest light interception (1193.8 Hz) was recorded in East direction at D4 and lowest (949.0 Hz) in the West at D1. Light interception in West and North directions was statistically lower than other directions. Light interception increased with increase in distance from the tree-stem. At 30 days after sowing (DAS), tallest plants were observed in West direction (23.08 cm) and shortest in the East (20.85 cm). The plant height at D1, D2 and D4 were statistically at par. At 30 DAS, lowest chlorophyll content (25.9) was observed in East direction at D4, whereas highest at 30 DAS in the West at D1 (31.5). At 90 DAS, significantly higher chlorophyll content was recorded in West direction and lowest in the South. Plants nearer to tree-stem showed high chlorophyll content. At 90 DAS, West and North directions recorded comparatively higher soil moisture, and among distances, it was recorded highest at D1. Among directions, highest grain yield was observed in East direction (210.1 g m-2) and lowest in the South (206.1 g m-2). The grain yield increased with distance from the tree trunk and significantly higher grain yield (4.68%) was recorded at D4 as compared to D1. From the findings, it can be concluded that the teak-barley agroforestry system, despite some significant above- and below-ground interactions affecting intercrop yield, may be a potential land-use system for adoption in the semi-arid region.